Improved Efficiency in Inverted Perovskite Solar Cells Employing a Novel Diarylamino‐Substituted Molecule as PEDOT:PSS Replacement. Issue 11 (15th March 2016) - Labban, Abdulrahman El; Chen, Hu; Kirkus, Mindaugas; Barbe, Jeremy; Del Gobbo, Silvano; Neophytou, Marios; McCulloch, Iain; Eid, Jessica
Abstract : An approach to fabricate high‐efficiency inverted planar perovskites solar cells using solution‐processed organic small molecules hole transporting layer is reported. Devices using CH3 NH3 PbI3 as photoactive layer and PC60 BM as electron transport layer show power conversion efficiencies exceeding 12% and open‐circuit voltages ( V OC ) higher than 1 V.